Environmentally friendly packaging materials based on thermoplastic starch - Ocelić Bulatović, Vesna (Array, 2019)
Low-density polyethylene (LDPE) is extensively used as packaging material, and as such has a short service life, but long environmental persistence. The alternative to reducing the impact of LDPE as packaging material on the environment is to blend it with carbohydrate-based polymers, like starch. Therefore, the focus of this investigation was to prepare bio-based blends of LDPE and thermoplastic starch (TPS) containing different amounts of TPS using a Brabender kneading chamber. Due to incompatibility of LDPE/ TPS blends, a styrene–ethylene/butylene–styrene block copolymer, grafted with maleic anhydride (SEBS-g-MA) containing 2 mol % anhydride groups, was added as a compatibilizer. The effect of the biodegradable, hydrophilic TPS, its content, and the incorporation of the compatibilizer on the properties of LDPE/TPS blends were analysed. The characterization was performed by means of thermogravimetric analysis (TG), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and water absorption (WA). Based on the results of the morphological structure, a good dispersion of the TPS phase in LDPE matrix was obtained with the incorporation of compatibilizer, which resulted in better thermal and barrier properties of these materials.